2019
DOI: 10.1017/s0142716419000341
|View full text |Cite
|
Sign up to set email alerts
|

Semantic integration declines independently of working memory in aging

Abstract: Semantic integration and working memory both decline with age. However, it remains unclear whether the semantic integration decline is independent of working memory decline or whether it can be solely explained by the latter factor. In this event-related potentials experiment, 43 younger adults and 43 cognitively healthy older adults read semantically congruent and incongruent sentences. After controlling for working memory, behavioral accuracy was significantly lower in the older adults than in the younger ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Searching through semantic memory for category-appropriate words takes older adults longer, not just because their cognitive abilities are slowed, but because they have a greater volume of semantic memory to search through. The suggestion that semantic access is slowed, but semantic abilities themselves are not impaired, is consistent with the robust finding of greater vocabulary size in older adults (e.g., Hardy et al, 2017;Hartshorne & Germine, 2015;Zhu et al, 2019) and, importantly, with the notion that an absence of semantic content in sentences increases older adults' sentence processing difficulties (Poulisse et al, 2019). The study by Poulisse et al (2019) found stronger age-related declines on agreement error detection measures for pseudoverbs compared to real verbs, suggesting that semantics may act as a type of compensation mechanism for impaired syntax processing.…”
Section: Sentence Comprehension In Ageing Populationssupporting
confidence: 81%
See 1 more Smart Citation
“…Searching through semantic memory for category-appropriate words takes older adults longer, not just because their cognitive abilities are slowed, but because they have a greater volume of semantic memory to search through. The suggestion that semantic access is slowed, but semantic abilities themselves are not impaired, is consistent with the robust finding of greater vocabulary size in older adults (e.g., Hardy et al, 2017;Hartshorne & Germine, 2015;Zhu et al, 2019) and, importantly, with the notion that an absence of semantic content in sentences increases older adults' sentence processing difficulties (Poulisse et al, 2019). The study by Poulisse et al (2019) found stronger age-related declines on agreement error detection measures for pseudoverbs compared to real verbs, suggesting that semantics may act as a type of compensation mechanism for impaired syntax processing.…”
Section: Sentence Comprehension In Ageing Populationssupporting
confidence: 81%
“…The natural interaction between these modules implies that older adults can compensate for impaired syntactic processing by prioritising semantic information. Older adults' greater semantic knowledge and vocabulary size (Hartshorne & Germine, 2015; Zhu et al, 2019) are, in this view, used to balance out WM issues in sentence comprehension. Evidence for this position was found by Poulisse et al (2019), as mentioned earlier, who discovered increased deficits and poorer performance on stimuli with an absence of semantic content (in this case, pseudowords) compared to real words.…”
Section: Conscious Task Demands and Processing Speedmentioning
confidence: 99%
“…Conversely, no significant effect of aging on the N1 and P2 amplitudes has been found (Gunter et al, 1992;Kutas et al, 1998). Finally, aging effects on the LPC effect elicited during an SSCT have been reported by Zhu et al (2018Zhu et al ( , 2019 and Xu et al (2017). The authors observed a significant LPC effect in elderly participants only.…”
Section: Healthy Aging Effects On Semantic Sentence Comprehensionmentioning
confidence: 87%
“…At word level, lexical-semantic knowledge (including categorical and associative relations) is retained with increasing age as shown by behavioral (Giffard et al, 2003) and electrophysiological priming studies (Cocquyt et al, 2022). At sentence level, behavioral results are more heterogeneous since both lower (Xu et al, 2017;Zhu et al, 2018Zhu et al, , 2019 and similar (or even higher) accuracy scores (Federmeier et al, 2010;Iragui et al, 1996) in elderly compared to young subjects have been reported. The latter heterogeneity is probably related to between-task differences in the required cognitive resources.…”
Section: Healthy Aging Effects On Semantic Sentence Comprehensionmentioning
confidence: 97%
See 1 more Smart Citation